A Diabetes Outcome Progression Trial (ADOPT): An international multicenter study of the comparative efficacy of rosiglitazone, glyburide, and metformin in recently diagnosed type 2 diabetes - Viberti, G; Kahn, SE; Greene, D; Herman, W; Zinman, B; Holman, R; Haffner, S; Levy, D; Lachin, J; Berry, R; Heise, M; Jones, N; et al. (2002)
OBJECTIVE - Therapies with metformin, sulfonylureas, or insulin improve glycemic control in the short term but do not prevent progressive islet β-cell failure or long-term deterioration in glycemia. Our goal was to evaluate, in patients recently diagnosed with type 2 diabetes (<3 years), the long-term efficacy of monotherapy with rosiglitazone on glycemic control and on the progression of pathophysiological abnormalities associated with type 2 diabetes as compared with metformin or glyburide monotherapy. RESEARCH DESIGN AND METHODS - A Diabetes Outcome Progression Trial (ADOPT) is a randomized, double-blind, parallel-group study consisting of a screening visit, a 4-week placebo run-in, a 4-year treatment period, and an observational follow-up of ∼3,600 drug-naïve patients with type 2 diabetes diagnosed within the previous 3 years. After run-in, patients will be randomized to rosiglitazone, glyburide, or metformin titrated to the maximum effective daily doses (8 mg rosiglitazone, 15 mg glyburide, or 2 g metformin). The primary outcome is time to monotherapy failure, defined as the time following titration to the maximal effective or tolerated dose when fasting plasma glucose exceeds 180 mg/dl (10 mmol/l). Secondary outcomes include measures of islet β-cell function, insulin sensitivity, dyslipidemia, changes in urinary albumin excretion, plasminogen activator inhibitor-1 antigen, fibrinogen, and C-reactive protein. Safety and tolerability will also be evaluated. Patient-reported outcomes and resource utilization data will be collected and analyzed. CONCLUSIONS - ADOPT will provide data on the effect of mechanistically differing treatment options on metabolic control, β-cell function, and markers of macrovascular disease risk in type 2 diabetes.